Inter-species entanglement of Bose–Bose mixtures trapped in optical lattices - Wei Wang (王 巍); Vittorio Penna; Barbara Capogrosso-Sansone (New Journal of Physics, 2016)
In the present work we discuss inter-species entanglement in Bose–Bose mixtures trapped in optical lattices. This work is motivated by the observation that, in the presence of a second component, the MI lobe shifts differently on the hole- and particle-side with respect to the Mott lobe of the single species system (Guglielmino et al 2010 Phys. Rev. A http://dx.doi.org/10.1103/PhysRevA.82.021601 82 http://dx.doi.org/10.1103/PhysRevA.82.021601 ; Capogrosso-Sansone et al 2011 Laser Phys. http://dx.doi.org/10.1134/s1054660x11150023 21 http://dx.doi.org/10.1134/s1054660x11150023 ). We use perturbation theory, formulated in a Hilbert space decomposed by means of lattice symmetries, in order to show that the nonuniform shift of the Mott lobe is a manifestation of inter-species entanglement which differs in the lowest excited states to remove and add a particle. Our results indicate that inter-species entanglement in mixtures can provide a new perspective in understanding quantum phase transitions. To validate our approach, we compare our results from perturbation theory with quantum Monte Carlo simulations.